Many-body effects and non-local charge fluctuations in the double perovskite Sr2FeMoO6. Issue 8 (22nd January 2018) - Martins, Henrique P.; Guedes, Eduardo B.; Mossanek, Rodrigo J. O.; Prado, Fernando D.; Caneiro, Alberto; Abbate, Miguel
Abstract : We studied the electronic structure of Sr2 FeMoO6 using core level and valence band photoemission. Abstract : We studied the electronic structure of Sr2 FeMoO6 using core level and valence band photoemission. The spectra were obtained using high energy X-rays of 1840 eV, which provide bulk sensitive information on the electronic structure. The experimental data were analyzed using the spectral weight from cluster model calculations. The ground state reveals a large Fe–O and Mo–O hybridization, as well as the importance of non-local Fe–O–Mo charge fluctuations. The latter is crucial to explain the half-metallic character attributed to the Sr2 FeMoO6 compound. The core level and valence band photoemission spectra show charge transfer satellites. These satellites are related to many-body effects and are larger for the Fe levels than for the Mo states.